Analysis of Syntactic Errors in Arabic Speech Texts during Muhadharah Activities at Pondok Pesantren Al-Iman Putri Ponorogo - Faiq Aulia Rakhman; Salsabila Fatima (LP3M Pascasarjana STAI Ibnurusyd, 2025)
The research problem refer to the errors made by students of Al-Iman Islamic Boarding School for female in writing Arabic speech text. These errors are an essential part of the Arabic language learning process. This study aims to identify the types of errors frequently encountered, understand their causes, and provide corrections for these Arabic language errors. The muhadharah activity at this Islamic boarding school is one of the activities that accommodates students in improving their Arabic language skills in speaking and writing. This research uses descriptive qualitative research methods, collecting data through observation, interview, and documentation techniques. The research results show that there are 5 syntactical errors in the Arabic speech texts of the students, including errors in writing maf'ul, isim, and khobar from 'amil nawasikh, athaf-ma'thuf, and khobar. Based on these syntactical errors, the most frequent error form is in the rules for writing isim and khobar from 'amil nawasikh.